(untitled) (Al Basirah, 2022)
Universally, Postcolonial literature initiates certain disciplines and numerous subject matters which were dared to speak before. In recent times observe the change in behaviors and approaches towards multiplicity, spiritual beliefs, and literature. Postcolonial literature also experiences the same fate in the form of its Postcolonial waves. In Postcolonial works, Muslim literati show their presence in every form of literature that the world has ever been observed. The reason behind such intelligentsia’s existence is that Muslims exist all around the world as Islam is the fastest-growing religion in the world. In this way, Muslim Postcolonialism under the umbrella of General Postcolonialism is projected to highlight the Muslim issues and concerns. Muslim Post-colonialists are the founders of twentieth-century Modern Post-colonialism, that extends to twenty-first century; the immense literature shows distinctive existence within the body of World Literature generally and General Postcolonial, particularly. Muslim Postcolonialism attempt to show the positive face of Islam to prove that Muslims are not terrorists, rather the victims of terrorism.